DESAIN APLIKASI POST DISCHARGE PLANNING ONLINE (PDPO) PASIEN COVID-19 MENGGUNAKAN USER CENTERED DESIGN UNTUK MENDUKUNG ERA NEW NORMAL (STUDI KASUS RSUD SYARIFAH AMBAMI RATO EBU BANGKALAN) - ACHMAD MASFI; NOVI PRASTITI (NHM PRESS, 2022)
The Covid-19 pandemic has had an impact on nursing services in hospitals, one of which is discharge planning. It can be that nurses have an important role in improving patient behavior by providing post discharge planning. The impact of COVID-19 is a challenge for health services. Thus, it is necessary to support and suppress patient mobility, especially post-Covid-19 patients in the health care area. This is in line with the government's policy regarding the era of adaptation to new habits. The method used in software design is the User Centered Design (UCD) method. This method is a method that establishes the user as the center of system design. The user-centred design approach (UCD) was successfully used to design the Post Discharge Planning Online (PDPO) application. In addition, it also succeeded in translating user needs obtained from the Forum Group Discussion (FGD). The prototype is then used to successfully create a design solution, which is then rated by 30 respondents. The result is that the application functions meet the user's needs.